2015
DOI: 10.1161/circulationaha.114.015231
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Single-Cell Analysis of Transplanted Human Induced Pluripotent Stem Cell–Derived Cardiomyocytes After Acute Myocardial Infarction

Abstract: Background Human induced pluripotent stem cells (iPSCs) are attractive candidates for therapeutic use, with the potential to replace deficient cells and to improve functional recovery in injury or disease settings. Here we test the hypothesis that human iPSC-derived cardiomyocytes (iPSC-CMs) can secrete cytokines as a molecular basis to attenuate adverse cardiac remodeling after myocardial infarction (MI). Methods and Results Human iPSCs were generated from skin fibroblasts and differentiated in vitro using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 42 publications
(42 reference statements)
0
56
0
Order By: Relevance
“…Recently, several studies have reported that iPSC-CMs provide functional benefit after myocardial infarction, although there has been no consensus about the protective mechanism induced by these differentiated cardiomyocytes (11). By using cardiac MRI and comparing with a nontreated control, Wu et al (12) found that iPSC-CMs promoted cardiac protection and attenuated cardiac remodeling after myocardial infarction, despite limited engraftment detected with bioluminescence imaging. In our present study, we found that the iPSC group and the iPSC-CM group showed a steady increase in 18 F-FDG accumulation during the 4-wk period whereas the ESC group showed a higher accumulation only in the earlier stage, indicating that iPSCs, especially iPSC-CMs, may produce a more stable therapeutic response than ESCs or ESC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that iPSC-CMs provide functional benefit after myocardial infarction, although there has been no consensus about the protective mechanism induced by these differentiated cardiomyocytes (11). By using cardiac MRI and comparing with a nontreated control, Wu et al (12) found that iPSC-CMs promoted cardiac protection and attenuated cardiac remodeling after myocardial infarction, despite limited engraftment detected with bioluminescence imaging. In our present study, we found that the iPSC group and the iPSC-CM group showed a steady increase in 18 F-FDG accumulation during the 4-wk period whereas the ESC group showed a higher accumulation only in the earlier stage, indicating that iPSCs, especially iPSC-CMs, may produce a more stable therapeutic response than ESCs or ESC-CMs.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of hESC-derived ECs injected into infarcted hearts was shown to be less than 10% at 1 week, and less than 1% at 8 weeks [33]. Similarly, hPSC-derived cardiomyocytes showed poor survival in ischemic hearts, usually disappearing within a month [34]. Even when cells were injected in a hindlimb ischemia model, the results were not much different.…”
Section: Use Of Biomaterials To Improve Cell Survival In Vivomentioning
confidence: 99%
“…The survival of hESC-ECs injected into ischemic hearts was not much different: < 10% of the injected cells survived at 1 week and 1% or less remained at 8 weeks 8 . hPSC-derived cardiomyocytes showed poor survival in ischemic hearts, with most of them disappearing usually within a month 9 . Similar trends were observed when cells were injected into a hindlimb ischemia model.…”
Section: Introductionmentioning
confidence: 99%